2010
DOI: 10.1097/ta.0b013e3181e84222
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence During Trauma Resuscitation: Ready for Primetime?

Abstract: Family members present during trauma resuscitation suffered no ill psychologic effects and scored equivalent to those family members who were not present on anxiety, satisfaction, and well-being measures. Quality of care during trauma resuscitation was maintained. The fact that all the family members would repeat experience again supports the idea that FPTR was not too traumatic for those who chose to be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 22 publications
1
50
0
5
Order By: Relevance
“…Emotional connectedness between patient and their relatives also emerged in these studies. 8 In addition, from the patient's perspective, Eichorn et al also revealed similar things that of from family members' point of view. 16 In their study, they used the Family Presence Patient Interview Guide (FPPIG) to interview nine purposive samples of patients in the emergency department of a university affiliated, regional, level 1 trauma centre in the USA.…”
Section: Patient-family Connectednessmentioning
confidence: 60%
See 1 more Smart Citation
“…Emotional connectedness between patient and their relatives also emerged in these studies. 8 In addition, from the patient's perspective, Eichorn et al also revealed similar things that of from family members' point of view. 16 In their study, they used the Family Presence Patient Interview Guide (FPPIG) to interview nine purposive samples of patients in the emergency department of a university affiliated, regional, level 1 trauma centre in the USA.…”
Section: Patient-family Connectednessmentioning
confidence: 60%
“…8 Interestingly, family members who were present during resuscitation scored better than those who were not present suggesting that they experienced less anxiety, greater satisfaction and better family wellbeing. 8 Mazer et al also reported from their descriptive study that there were 49.3% of family members which were randomly selected to participate in a telephone survey desired to be present during resuscitation. 9 In…”
Section: Theme 1: Patient and Family Members' Preferencesmentioning
confidence: 99%
“…1,22,26,27,[31][32][33][34][35] Several studies have highlighted the benefits of family presence without interference in patient care. 16,[36][37][38][39] Health care providers working in pediatric trauma resuscitation may gain knowledge from the findings of both parental groups studied. Family members in our study identified the importance of not interfering with the care their child receives.…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing support for a designated family support person with many studies suggesting that it is essential for successful implementation of a family presence during resuscitation program [18,[27][28][29] . However in practice, designating a family support person remains low on the priority list.…”
Section: Discmentioning
confidence: 99%